2004
DOI: 10.1016/s1054-139x(04)00070-9
|View full text |Cite
|
Sign up to set email alerts
|

Reading nutrition labels and fat consumption in adolescents

Abstract: We studied the relationship between reading nutrition labels and percent calorie intake from fat. In adolescent boys, reading nutrition labels was associated with higher fat intake. In girls, fat intake did not differ by frequency of nutrition label reading. Nutrition label reading does not translate into healthier diet in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 0 publications
4
43
0
Order By: Relevance
“…This partially explains why obesity was associated with nutrition label use only among men, but not among women, once the effect of body weight change had been taken into account. Similar findings were also reported among adolescents where results indicated that reading nutrition labels was associated with higher fat intake among boys, but not among girls (23). …”
Section: Discussionsupporting
confidence: 81%
“…This partially explains why obesity was associated with nutrition label use only among men, but not among women, once the effect of body weight change had been taken into account. Similar findings were also reported among adolescents where results indicated that reading nutrition labels was associated with higher fat intake among boys, but not among girls (23). …”
Section: Discussionsupporting
confidence: 81%
“…Other studies have also shown that nutrition label reading and food education do not translate into healthier diet in adolescents. 22,23 Therefore, it might be necessary for intervention programmes designed for adolescents to focus not only on education on healthy food eating but also on behaviour changes. These programmes should also take into account the adolescents' lifestyle and social environment.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed benefits of providing increased nutritional information to consumers included the possibility that increased knowledge about the nutrition and fat content of food would be associated with a healthier overall dietary intake in adults and children. Previous studies with adults have found that increased label use is associated with lower fat intake (Neuhouser et al 1999).The use of food labels has also been associated with fat reduction efforts in adults trying to make healthful dietary changes (Kristal et al 1998), and the total percentage of calories from fat has been associated with reading nutrition labels (Huang et al 2004). Recent data also suggest that the use of the nutrition facts panel has increased in recent years (from 32% in 2004 bs_bs_banner DOI: 10.1111DOI: 10.…”
Section: Background Nutritional Labels In the United Statesmentioning
confidence: 99%